Application of Natural Language Processing for Improved Information Retrieval in University Libraries in Kebbi State - Kaoje, Sahabi Abubakar; Saidu, Anas; Aminu, Murtala (Information Research Communications, 2025)
This study looked into how Natural Language Processing (NLP) can improve information retrieval in university libraries in Kebbi State. A descriptive survey design was used, focusing on 38 processing and ICT librarians from three institutions: AFUSTA, FUBK, and FUAZ. Data were collected through a structured Google Form questionnaire and analyzed using descriptive statistics. The findings showed clear weaknesses in current search systems, especially in dealing with natural language queries and providing relevant results. Respondents pointed out NLP techniques, such as semantic search and query expansion, as good solutions for improving search efficiency and accuracy. Although there was general awareness of the benefits of NLP, the readiness for adoption varied due to issues with infrastructure, training, and policy support. The study concludes that with targeted investment in technology, staff development, and institutional planning, NLP can greatly enhance information retrieval services in Nigerian university libraries.
Keywords: Natural Language Processing (NLP); Information Retrieval (IR); University Libraries; Kebbi State University; Semantic Search; Query Expansion and Relevance Ranking